What do employee referral programs do? Measuring the direct and overall effects of a management practice - Guido Friebel; Matthias Heinz; Mitchell Hoffman; Nick Zubanov (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Employee referral programs (ERPs) are randomly introduced in a grocery chain. On direct effects, larger referral bonuses increase referral quantity but decrease quality, though the increase in referrals from ERPs is modest. However, the overall effect of having an ERP is substantial, reducing attrition by 15% and significantly decreasing labor costs. This occurs, partly, because referrals stay longer than non-referrals, but, mainly, from indirect effects: non-referrals stay longer in treated than in control stores. The most-supported mechanism for these indirect effects is workers value being involved in hiring. Attrition impacts are larger in higher-performing stores and better local labor markets.
Keywords: M51; M52; D23; 330; Management practices; organizational economics; hiring; respect